(untitled) (Research, Society and Development, 2022)
This paper aims to analyse the influence of the territory on political organisation of United Kingdom, particularly from the perspective of its withdrawal from European Union, through the process that became known as Brexit, which had as relevant cause the immigration process. This paper starts from the configuration of the United Kingdom as a State, and the sequence studies the way in which the United Kingdom became a member of the European Union until its effective exit of the State from the European bloc. Finally, the research deals with the effects that withdrawal will create on the territory of the United Kingdom. The work emphasizes the aspects on the Scottish separatist movement, the Irish boarders and the immigration. The paper works on the historical-deductive method from the concepts to apply them on the case. The results of the research indicate that que causes of the Brexit will not be eliminated with the Brexit, so the United Kingdom will face a challenge in keeping its territorial unity.